2016
DOI: 10.1090/jams/866
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of sandpile groups of random graphs

Abstract: Abstract. We determine the distribution of the sandpile group (a.k.a. Jacobian) of the Erdős-Rényi random graph G(n, q) as n goes to infinity. Since any particular group appears with asymptotic probability 0 (as we show), it is natural ask for the asymptotic distribution of Sylow p-subgroups of sandpile groups. We prove the distributions of Sylow p-subgroups converge to specific distributions conjectured by Clancy, Leake, and Payne. These distributions are related to, but different from, the Cohen-Lenstra dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 77 publications
4
128
0
Order By: Relevance
“…Theorem 1 follows from Theorem 2 using the results of Wood [22] on the moment problem. The general question is the following.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Theorem 1 follows from Theorem 2 using the results of Wood [22] on the moment problem. The general question is the following.…”
Section: Introductionmentioning
confidence: 97%
“…This is exactly the distribution appearing in Theorem 1. Note that this is not the original formula given in [5], but it can be easily deduced from it, see [22]. Here, a map φ :…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on this, D. Wagner conjectured [35] that almost every connected simple graph has a cyclic critical group. A recent study [37] concluded that the probability that the critical group of a random graph is cyclic is asymptotically at most…”
Section: Multiplying Any Row/column By ±1mentioning
confidence: 99%